ON THE FORMATION OF THE READYNESS OF THE FUTURE OF TEACHERS OF HUMANITARIAN CYCLE SUBJECTS USE OF CURRICULA IN PROFESSIONAL ACTIVITY (Pedagogy of Higher and Secondary Education, 2022)
Determination o f pedagogical programmatic facilities programmatic facilities o f the educational setting is resulted in the article, specified essence of readiness of future teachers of the articles of humanitarian cycle to application of the educational programs in professional activity, found out its structure and certain criteria.